PENGEMBANGAN KEMAMPUAN INDUSTRI KREATIF VIDEO DI KAMPUNG KOTA - Obed Bima Wicandra; , Erandaru; Gunawan Tanuwidjaja; Budi Prasetyadi; Linda Octavia (Institute of Research and Community Outreach - Petra Christian University, 2013)
This article provides description of public services project carried out by the Petra's Department of Architecture and the Department of Visual Communication Design under the full support from Petra's Research & Public Service Institution. The main activities of this project are video production training and video screening for Bratang Tangkis community. The main target for this project is people living in the Kampung of Bratang Tangkis, Barata Jaya and Kendangsari. They were chosen as a result of PCU collaboration with The Residents of Surabaya's River Bank Community within the platform of Ayorek! The residents feel the need to proactively document their living environment potential, an activity that is related with the development of local economy and in-line with the nation's strategy to develop creative economy. The training material is performing participative video recordings of wedding ceremonies and traditional events that took place within the kampung, followed with training on video transfer and editing.